Neuronal miR-29a protects from obesity in adult mice - Ma, Yuan; Murgia, Nicola; Liu, Yu; Li, Zixuan; Sirakawin, Chaweewan; Konovalov, Ruslan; Kovzel, Nikolai; Xu, Yang; Kang, Xuejia; Tiwari, Anshul; Mwangi, Patrick Malonza; Sun, Donglei; et al. (Molecular metabolism, 2022)
Objective - Obesity, a growing threat to the modern society, represents an imbalance of metabolic queues that normally signal to the arcuate hypothalamic nucleus, a critical brain region sensing and regulating energy homeostasis. This is achieved by various neurons many of which developmentally originate from the proopiomelanocortin (POMC)-expressing lineage. Within the mature neurons originating from this lineage, we aimed to identify non-coding genes in control of metabolic function in the adulthood. - Methods - In this work, we used microRNA mimic delivery and POMCCre-dependent CRISPR-Cas9 knock-out strategies in young or aged mice. Importantly, we also used CRISPR guides directing suicide cleavage of Cas9 to limit the off-target effects. - Results - Here we found that mature neurons originating from the POMC lineage employ miR-29a to protect against insulin resistance obesity, hyperphagia, decreased energy expenditure and obesity. Moreover, we validated the miR-29 family as a prominent regulator of the PI3K-Akt-mTOR pathway. Within the latter, we identified a direct target of miR-29a-3p, Nras, which was up-regulated in those and only those mature POMCCreCas9 neurons that were effectively transduced by anti-miR-29 CRISPR-equipped construct. Moreover, POMCCre-dependent co-deletion of Nras in mature neurons attenuated miR-29 depletion-induced obesity. - Conclusions - Thus, the first to our knowledge case of in situ Cre-dependent CRISPR-Cas9-mediated knock-out of microRNAs in a specific hypothalamic neuronal population helped us to decipher a critical metabolic circuit in adult mice. This work significantly extends our understanding about the involvement of neuronal microRNAs in homeostatic regulation.
Available online 29 April 2022
Gesehen am 06.07.2022